Effects of Using Hashtag, Celebrity Endorsement and Paid Promotion Objective Achievement in Instagram (Case Study:Women Fashion Brand) - Lestari, Susi; Aldianto, Leo (Journal of Innovation, Business and Entrepreneurship, 2016)
Abstract.The effort of promotion through Instagram doesn’t significantly affect the objective of promotion if brand can’t understand effective promotion tool and can influence audiences in their process of recognizing brand until deciding to buy a product of the brand. There are some promotion tools that can be effectively optimized to influence that process. Based on interview with 10 women who are active Instagram users, it was known that the use of hashtag, celebrity endorsement, and paid promote can effect their process of recognizing until making decision to buy a product of a brand. The objective of the research is to estimate the effect of using hashtag, celebrity endorsement, and paid promote in Instagram women fashion brand to promotion objective achievement. Research was executed in Bandung. By using Probability Sampling Purposive Technic, questionnaires in the effect of using hashtag, celebrity endorsement, and paid promote to promotion objective achievement (concern of brand, connection of brand to intention of buying) were given to 100 18-30 years old active women Instagram users who like to search for information about women fashion brands through Instagram. The responses were recorded in Microsoft Excel to be tested for validity and reliability by using statistic methods. Then, data were analyzed by using Path Analysis to understand the connection of variables and their effect to promotion objective achievement. The result showed that the use of hashtag and celebrity endorsement significantly affect short promotion objective achievement, then the use of paid promote minimally affect short promotion objective. Hashtag, Celebrity Endorsement and Paid Promote significantly affect long promotion objective achievement. Keywords: Social Media Objective, Instagram, Hashtag, Celebrity Endorsement, Paid Promote